Evidence for habitat and climatic specializations driving the long‐term distribution trends of UK and Irish bumblebees. Issue 8 (5th June 2015) - Casey, L. M.; Rebelo, H.; Rotheray, E.; Goulson, D.; Beggs, Jacqueline
Abstract Aim There is widespread concern over the current state of global pollinator populations; however, lack of monitoring means patterns of decline are not well characterized. We aimed to investigate the influence of habitat and climate specializations on bumblebee distribution trends over time using long‐term species data. Location Our study is based on data from the UK and Ireland, for which the most comprehensive set of bumblebee records exists. Previous analysis of the UK data highlighted severe range contractions for a number of species by the 1980s. Methods We use the most current dataset to quantify the extent of range change over three time periods (pre‐1960, 1960–80 and 1981–2012) and to investigate whether species are becoming more marginal, that is occupying areas with more extreme or specialized climatic conditions within the UK and Ireland. For species that have contracted or become more marginal, we predict their climatic specialization within the UK and Ireland using Maxent models, allowing us to associate records with climatic suitability values for each time period and to investigate whether or not species are contracting towards their climatic optimum. Results We find that populations of most rare bumblebee species appear to have stabilized post‐1980, while the more common species appear to have expanded in range. However, rare species tend to have become more marginal in the sites they occupy post‐1980, some have contracted towards their predicted climatic optimum and some of which also retracted towards coastal areas. Main conclusions Our results provide a mixed picture of the state of the UK and Ireland's bumblebee fauna, and must be interpreted with caution as changing patterns of recorder effort may distort real trends. They highlight the need for future monitoring of the abundance of pollinators on both a regional and global scale.